PHARMACOECONOMIC EVALUATION OF TREATMENT OF SECONDARY HYPERPARATHYROIDISM IN PATIENTS ON DIALYSIS WITH CINACALCET - R. I. Yagudina; V. G. Serpik (Фармакоэкономика, 2015)
Abstract: the pharmacoeconomic study compared the standard drug therapy (vitamin D and phosphorbinders) of secondary hyperparathyroidism (SHPT) to the using a combination of Mimpara (Cinalcet), vitamin D and phosphorbinders in patients with end-stage renal disease on dialysis. Comparison was carried out by mean of «cost-efficacy» analysis, as the main performance indicator has been selected % of patients reaching the target values of K / DOQI of the main biochemical parameters - parathyroid hormone level and CaxP. The use of Mimpara demonstrated advantages over standard treatment of secondary hyperparathyroidism to reduce the complications of the cardiovascular system and musculoskeletal system, reduce the dose of vitamin D and advantages in terms of «cost-efficacy» analysis. The cost of achieving the goals of treatment (values of K / DOQI of the main biochemical parameters) in one patient for the time horizon of 26 weeks of the first year of treatment for a combination of Mimpara, vitamin E and drugs phosphorbinders was 20,709 rubles. (Taking into account the costs of dialysis treatments), and for standard therapy - 110,092 rubles (Taking into account the costs of dialysis treatments). Thus, treatment of SHPT combination of vitamin D, drugs and phosphorbinders and Mimpara can be considered as an alternative to the dominant position of pharmacoeconomic analysis in comparison to therapy with vitamin D and phosphorbinders only.